Referensi dan Fungsi Makian dalam Film “Jakarta vs Everybody”: Kajian Sosiolinguistik - Wahyuni Alawiyah (Universitas Islam Sumatera Utara, 2026)
This study examines the reference and functions of swear words in the film Jakarta vs Everybody through a sociolinguistic approach, addressing how such expressions reflect speakers’ psychological states and the broader social realities represented in the narrative. Employing a qualitative design with document analysis techniques, the data were collected from film dialogues containing swear words and subsequently classified based on categories of reference proposed by Wijana and Rohmadi (2006) and functional typology developed by Anderson and Trudgill (1992). The analysis identifies 48 instances of swear expressions encompassing six referential types, namely states, animals, body parts, activities, objects, and professions. Among these, state-related references appear most frequently, indicating their prominent use in negatively evaluating mental conditions or behavioral traits. In terms of function, three primary categories emerge: abusive, expletive, and humorous, with abusive function dominating the data. This predominance demonstrates that swear words are primarily utilized to attack, demean, and convey disapproval, while simultaneously constructing and reflecting the harshness of urban social realities depicted in the film.